Simulations Study of Blast Wall Effectiveness: Comparing Concrete and Polymer Composites in Pressure Wave Mitigation - Nur Farhana Zaid Azuan,; Abdulhafid M. A. Elfaghi, (Journal of Advanced Mechanical Engineering Applications, 2025)
Walls play a crucial role in protecting structures and people from explosion hazards, especially in industrial and military environments. This study examines the blast resistance performance of T-shaped wall constructed from concrete composite (CONC-35MPa) and polymer matrix composite (PMC, EPOXY RES) materials using ANSYS Explicit Dynamics simulations. The concrete wall showed a maximum deformation of 0.97m about half that of the epoxy composite’s 1.92m, and experienced peak shear stresses up to 1.2GPa at critical joints. Directional velocity reached 3651 m/s for concrete versus 6139m/s for the polymer composite, demonstrating concrete’s superior stiffness and energy absorption. These results confirm that concrete provides better resistance to blast induced deformation and stress. Comparing to most studies that look at fiber-reinforced concrete or polymer composites separately, this work combines material behavior and structural geometry in a single explicit dynamics simulation. It offers practical improvements like reinforcement methods and shape changes for T-shaped walls, backed by clear blast response data. The study also suggests future research on adding sensors for real time blast monitoring, a topic rarely covered before. Overall, it links material mechanics with engineering design to help create safer, stronger protective structures using validated simulations for real blast conditions.